"By all means let us complete the exercise": the 50‐year search for Lapita on Aneityum, southern Vanuatu and implications for other "gaps" in the Lapita distribution. Issue 2 (24th June 2016) - BEDFORD, STUART; SPRIGGS, MATTHEW; SHING, RICHARD
ABSTRACT: Archaeological research on the island of Aneityum, the southernmost inhabited island of the Vanuatu archipelago (the former New Hebrides), began in 1963 under the direction of Richard and Mary Shutler. It was soon after this that William Dickinson began analysing pottery sherds from various sites across the archipelago. He ultimately went on to study hundreds of samples, including – most recently – 112 from the site of Teouma on Efate Island. Early pottery sites remained elusive in the southern islands for two decades after the Shutlers' pioneering work and on Aneityum for nearly 50 years. Assessments of the island's geomorphology, a key aspect regularly emphasised by Dickinson, coupled with perseverance and some serendipitous test‐pitting finally led to the discovery of a Lapita site on Aneityum. Dickinson's petrographic expertise was once again called on some 50 years after research first started on the island, to contribute to initial identification of the site's significance. We examine the difficulty of finding Lapita on Aneityum through a historical lens in order to reflect back on other presumed Lapita "gaps" that remain today, such as in much of the main Solomons' chain and – with one current exception – in Samoa. Perhaps the gaps in other regions are not as extensive as is often argued.